2017
DOI: 10.1080/14992027.2017.1308565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a wireless remote microphone in bimodal cochlear implant recipients

Abstract: Objective: To evaluate the benefit of a wireless remote microphone (MM) for speech recognition in noise in bimodal adult cochlear implant (CI) users both in a test setting and in daily life. Design: This prospective study measured speech reception thresholds in noise in a repeated measures design with factors including bimodal hearing and MM use. The participants also had a 3-week trial period at home with the MM. Study sample: Thirteen post-lingually deafened adult bimodal CI users. Results: A significant imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
3
14
0
6
Order By: Relevance
“…Other advanced remote wireless microphone systems, Mini Microphones 1 and 2þ, also enabled a significant improvement of speech recognition in noise in unilateral or bilateral CI recipients as well as bimodal CI-HA users (De Ceulaer et al, 2017 6 ). In bimodal recipients, the application of Mini Microphone 2þ on both the CI and HA yielded a significant improvement compared with unilateral use with the CI only (Vroegop et al, 2017 24 ). Furthermore, the benefits of remote wireless microphone systems were shown for pediatric unilateral and bilateral CI recipients with bilateral hearing loss (Schafer and Thibodeau, 2006 19 ; Razza et al, 2017 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other advanced remote wireless microphone systems, Mini Microphones 1 and 2þ, also enabled a significant improvement of speech recognition in noise in unilateral or bilateral CI recipients as well as bimodal CI-HA users (De Ceulaer et al, 2017 6 ). In bimodal recipients, the application of Mini Microphone 2þ on both the CI and HA yielded a significant improvement compared with unilateral use with the CI only (Vroegop et al, 2017 24 ). Furthermore, the benefits of remote wireless microphone systems were shown for pediatric unilateral and bilateral CI recipients with bilateral hearing loss (Schafer and Thibodeau, 2006 19 ; Razza et al, 2017 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral, bimodal, and bilateral CI recipients obtained a benefit in speech recognition when using either of the two Mini Microphones, and a better speech performance with the Mini Microphone 21 compared with the Mini Microphone 1 (De Ceulaer et al, 2017). Vroegop et al (2017) compared speech perception in bimodal adult CI recipients for different applications of the Mini Microphone 21. Bimodal use of the Mini Microphone 21 yielded a significant improvement compared with unilateral use with the CI only.…”
Section: Introductionmentioning
confidence: 99%
“…By acquiring the signal at or near the source, the signal-tonoise ratio (SNR) at the listener's ear is improved and consequently the negative effects of ambient noise, as well as those of distance and reverberation, are reduced. Previous research has shown considerable improvement in unilateral CI users' speech recognition in noise (De Ceulaer et al 2016;Razza et al 2017;Schafer and Thibodeau 2004;Schafer et al 2009;Vroegop et al 2017;Wolfe et al 2015a;Wolfe, Morais, and Schafer 2015b). A directional mode of the wireless microphone would possibly improve speech recognition even more, but specific, comparative data is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A directional mode of the wireless microphone would possibly improve speech recognition even more, but specific, comparative data is lacking. The previously mentioned studies used either an omnidirectional mode of the wireless microphone (Razza et al 2017;Vroegop et al 2017;Wolfe, Morais, and Schafer 2015b), an adaptive mode changing between omnidirectional and directional depending on the amount of the background noise (De Ceulaer et al 2016), or a directional mode (Schafer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation